2021
DOI: 10.1101/2021.11.24.21266793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Language Model for Automatic Identification of Intimate Partner Violence Reports from Twitter

Abstract: BackgroundIntimate partner violence (IPV) is a preventable public health issue that affects millions of people worldwide. Approximately one in four women are estimated to be or have been victims of severe violence at some point in their lives, irrespective of their age, ethnicity, and economic status. Victims often report IPV experiences on social media, and automatic detection of such reports via machine learning may enable the proactive and targeted distribution of support and/or interventions for those in n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In a sense, internet forums can be seen as unregulated "virtual focus groups" [29] since there is no interference from researchers and potential in uence on thought expression. Hence, internet forums can be regarded as reliable sources of "natural data" and have proved to be valuable platforms for researchers to explore sensitive and stigmatized issues, such as intimate IPV and sexual abuse, using various online platforms like Weibo, Twitter, and forums [30,31]. As of August 2023, the latest o cial statistics reported that China had a total of 1.079 billion internet users, with an internet penetration rate of 76.4% [32].…”
Section: Methodsmentioning
confidence: 99%
“…In a sense, internet forums can be seen as unregulated "virtual focus groups" [29] since there is no interference from researchers and potential in uence on thought expression. Hence, internet forums can be regarded as reliable sources of "natural data" and have proved to be valuable platforms for researchers to explore sensitive and stigmatized issues, such as intimate IPV and sexual abuse, using various online platforms like Weibo, Twitter, and forums [30,31]. As of August 2023, the latest o cial statistics reported that China had a total of 1.079 billion internet users, with an internet penetration rate of 76.4% [32].…”
Section: Methodsmentioning
confidence: 99%